Corporate Social Responsibility, Stakeholder Engagement, and Universities - Aversano, Natalia; Sannino, Giuseppe; Polcini, Paolo Tartaglia; Nicolò, Giuseppe (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
The present book contributes to the public administration literature by providing new insights into corporate social responsibility (CSR), sustainability initiatives, and stakeholder engagement in the higher education context. The fourteen papers published in this Special Issue discuss the role of public universities in promoting sustainability actions, university missions, and Sustainable Development Goals (SDGs) embedded in the 2030 UN Agenda. In each contribution, avenues for research are suggested and, most importantly, stronger analytical connections are advocated between these inter-related research areas. In more detail, two papers focus their attention on university transparency and the processes' complexity in public institutions. Furthermore, two papers focus on CSR teaching and education, three papers analyze universities' social responsibility initiatives, and five papers focus on the SDGs. Lastly, taking into account how social networks have changed university communication and become powerful tools for building relationships with stakeholders, two papers of the Special Issue consider social media's role in university communications.